Graduate Students in Data Science Consulting : A Blueprint for Success - Emily H. Griffith; Mara Rojeski Blake; David J. Edwards; Shannon Ricci; Michelle Thompson Gumbs; Kate Freeman; Joddy Marchesoni (Chapman and Hall/CRC, 2026)
This manual provides a practical guide on how graduate students can work in statistical and data science consulting and offers valuable resources for anyone interested in creating, expanding, or maintaining statistical or data science consulting programs in higher education across multiple disciplines.Key Features: Hands on, practical guide to working with graduate students in data science consulting programs Broadly applicable across disciplines and program types Based on years of experience successfully working with graduate students as data science consultants This book is aimed at readers looking to set up a consulting program with their graduate students, as well as graduate students looking to consult during their studies.A PDF version of this book is available for free in Open Access at www.taylorfrancis.com. It has been made available under a Creative Commons Attribution- NonCommercial-ShareAlike (CC-BY-NC-SA) 4.0 license.